Paul's message and ministry in covenant perspective : selected essays - Hafemann, Scott J. (Eugene, Oregon : Cascade Books, 2015)
A collection of previously published exegetical essays.
Paul and his interpreters since F.C. Baur -- Reading Paul's [DIKAIO]-language: a response to Douglas Campbell's "Rereading Paul's [DIKAIO]-language" -- Paul's "history-of-redemption" use of the Old Testament in 2 Corinthians -- The comfort and power of the gospel: the argument of 2 Corinthians 1-3 -- The glory and veil of Moses in 2 Corinthians 3:7-14: an example of Paul's contextual exegesis of the Old Testament -- The sum of the matter: Paul's understanding of perseverance -- Paul's "Jeremiah" ministry in reverse and the reality of the new covenant -- "Because of weakness" (Gal 4:13): the role of suffering in the mission of Paul -- Pastoral suffering: recovering Paul's model of ministry in 2 Corinthians -- The "temple of the spirit" as the inaugural fulfillment of the new covenant -- Paul's concern for the unity of the church: an embodiment of his new covenant theology -- Divine judgment and the completion of the missionary task: Paul's motivation for ministry in 1-2 Thessalonians -- The sum of the ministry: challenges to Paul's exclusive gospel.
Includes bibliographical references (pages 201-208).
Keywords: Paul, -- the Apostle, Saint; Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Covenants -- Biblical teaching